The effect of employee mindfulness in the new media industry on innovative behavior: The chain mediating role of positive emotion and work engagement - Kuang, Ting Yue; Hu, Yue; Lu, Yan (Frontiers in Psychology, 2022)
Mindfulness has long been concerned and emphasized by scholars in the field of psychology, but there is still a lack of research on mindfulness in management in China. In this study, a questionnaire survey was conducted among 483 employees in the new media industry in Beijing, Shanghai, Guangzhou, Shenzhen and Hangzhou, China. After modeling and analysis, it was found that employee mindfulness has a positive influence on innovative behavior. Employee mindfulness and innovative behavior are mediated by positive emotions. Employee mindfulness and innovative behavior are mediated by work engagement. Employee mindfulness and innovative behavior are mediated by a chain of positive emotions and work engagement. Enterprise managers should improve the level of mindfulness of employees in the new media industry through mindfulness training and courses for mindfulness training, create an organizational environment that can arouse positive emotions and improve the positive emotions of employees, pay attention to arousing the enthusiasm of the staff, and promote the innovative behavior of staff while enhancing work engagement.